Black beauty - Sewell, Anna 1820-1878; Davage, Jonh (Harlow : Pearson Education, 2008)
Always be good, so people will love you. Always work hard and do your best. These were the words of Black Beauty's mother to her son when the two horses lived with Farmer Grey. But when Black Beauty got oider, this was sometimes very difficult for him. Not everybody was as kind as Farmer Grey.
Keywords: Novela inglesa -- Siglo XIX; Caballos -- Novela